Proteomic analysis of Pseudogymnoascus spp. From different geographical regions in response to temperature variation / Nurlizah Abu Bakar - Nurlizah , Abu Bakar (2021)
The need for understanding the detrimental effects of environmental stress for soil microorganisms is becoming more significant with current global warming issues. Temperature may alter the abundance of species in soil ecosystems, leading to consequential changes in microbial communities. Under temperature stress, fungi undergo numerous physiological changes in their proteome in order to survive. Understanding the changes in fungal proteomes can give insights into the complex protein responses that occur under high and low temperature stress. Mass spectrometry (MS)-based proteomics is a powerful tool that has helped researchers to identify and quantify complex protein mixtures in various cell systems. Pseudogymnoascus, a soil fungal genus that occurs in polar and temperate regions, is also a known producer of many extracellular hydrolase enzymes that contribute to soil decomposition. It is not known whether the mechanisms of temperature stress response of Pseudogymnoascus spp. differ in strains isolated from different regions and exposed to different environmental conditions. In this study, Pseudogymnoascus was chosen as a model taxon to characterise changes in fungal proteomic profiles in response to temperature stress. Analyses of the thermal tolerance and sensitivity of six isolates of Pseudogymnoascus spp. were carried out using temperature-dependent growth studies and colony morphological changes. Description of proteome profiles of Pseudogymnoacus spp. cultured at a non-stressful temperature (15°C) was carried out using liquid chromatography tandem mass spectrometry (LC MS/MS) to provide baseline information and knowledge of the phenotypic diversity of all six isolates. Bioinformatic analyses of differentially expressed proteins and Gene Ontology (GO) enrichment were used to identify the pathways that were significantly enriched in response to temperature variation (cold and heat stress studies). All six isolates were characterised as psychrotolerant fungi with lower and upper temperature limits for growth of 5°C and 25°C, respectively. The proteome profiles of all six isolates showed that the majority of proteins identified were clustered into groups representing metabolic functions and catalytic activities. Temperature stress response of Pseudogymnoascus spp. involved a wide range of pathways being enriched, with no suggestion of response mechanisms following specific geographical patterns. The data obtained in this study provide new information on how Pseudogymnoascus spp. respond to temperature variation in their environment and increase our understanding of how these temperature stress responses in the context of global climate change may affect decomposition processes in soil